STRATEGI GURU MADRASAH TSANAWIYAH NEGERI SALATIGA DALAM INSERSI KURIKULUM BERBASIS CINTA - Apriana, Rizzal Rizqi; Abshar, Muhammad Umar Ulil Aidi; Yani, Arum Pebri; Sulistyowati, Dwi; Susilawati, Ulfah (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This study examines the strategies used by teachers at Madrasah Tsanawiyah Negeri (MTsN) Salatiga in integrating the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) into the teaching and learning process, specifically in seventh-grade classrooms. The research aims to identify the practical approaches implemented by teachers to foster love-based values in students and to analyze the challenges encountered during the implementation of this curriculum innovation. A qualitative descriptive method was employed, involving classroom observations, interviews with teachers, and documentation analysis to obtain a comprehensive understanding of teaching practices. The findings show that teachers apply various methods such as modeling compassionate behavior, integrating affective values into learning materials, strengthening teacher-student relationships, and promoting collaborative learning environments. However, the implementation still faces several obstacles, including limited teacher training, varied student characteristics, insufficient learning media, and time constraints due to curricular demands. Despite these challenges, teachers demonstrate a strong commitment to cultivating emotional and spiritual development in students. This study concludes that the integration of a Love-Based Curriculum contributes positively to character formation and supports a more humanistic Islamic education model, although continuous professional development and institutional support are required to optimize the implementation. ABSTRAKPenelitian ini bertujuan mengkaji strategi guru di Madrasah Tsanawiyah Negeri (MTsN) Salatiga dalam menginsersikan Kurikulum Berbasis Cinta (KBC) ke dalam proses pembelajaran pada kelas VII serta mengidentifikasi tantangan yang muncul dalam pelaksanaannya. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data berupa observasi kelas, wawancara dengan guru, dan studi dokumentasi untuk memperoleh gambaran yang komprehensif terkait praktik pembelajaran. Hasil penelitian menunjukkan bahwa guru menerapkan berbagai strategi, antara lain memberi keteladanan sikap penuh kasih, mengintegrasikan nilai afektif dalam materi pelajaran, memperkuat relasi guru–siswa, serta menciptakan suasana belajar kolaboratif. Namun, implementasi KBC masih menghadapi beberapa hambatan seperti keterbatasan pelatihan guru, karakteristik siswa yang beragam, minimnya media pembelajaran pendukung, serta keterbatasan waktu akibat padatnya tuntutan kurikulum. Meskipun demikian, guru tetap berkomitmen dalam menumbuhkan perkembangan emosional dan spiritual peserta didik. Penelitian ini menyimpulkan bahwa insersi Kurikulum Berbasis Cinta memberikan kontribusi positif terhadap pembentukan karakter dan mendukung model pendidikan Islam yang lebih humanis, namun perlu adanya dukungan berkelanjutan dan penguatan kapasitas guru agar pelaksanaannya lebih optimal.